Dietary protein and the glycemic index handle insulin resistance within a nutritional program for avoiding weight regain after energy-restricted induced weight loss - Vidal-Ostos, F; Ramos-Lopez, O; Jebb, SA; Papadaki, A; Pfeiffer, AFH; Handjieva-Darlenska, T; Kunešová, M; Blaak, EE; Astrup, A; Martinez, JA (BioMed Central, 2022)
Background and aim: The role of dietary protein and glycemic index on insulin resistance (based on TyG index) within a nutritional program for weight loss and weight maintenance was examined. Methods: This study analyzed 744 adults with overweight/obesity within the DIOGenes project. Patients who lost at least 8% of their initial weight (0–8 weeks) after a low-calorie diet (LCD) were randomly assigned to one of five ad libitum diets designed for weight maintenance (8–34 weeks): high/low protein (HP/LP) and high/low glycemic index (HGI/LGI), plus a control. The complete nutritional program (0–34 weeks) included both LCD plus the randomized diets intervention. The TyG index was tested as marker of body mass composition and insulin resistance. Results: In comparison with the LP/HGI diet, the HP/LGI diet induced a greater BMI loss (p < 0.05). ∆TyG was positively associated with resistance to BMI loss (β = 0.343, p = 0.042) during the weight maintenance stage. In patients who followed the HP/LGI diet, TyG (after LCD) correlated with greater BMI loss in the 8–34 weeks period (r = −0.256; p < 0.05) and during the 0–34 weeks intervention (r = −0.222, p < 0.05) periods. ΔTyG1 value was associated with ΔBMI2 (β = 0.932; p = 0.045) concerning the HP/LGI diet. Conclusions: A HP/LGI diet is beneficial not only for weight maintenance after a LCD, but is also related to IR amelioration as assessed by TyG index changes. Registration Clinical Trials NCT00390637.